Vertical takeoff and landing wing developed for long distance flight and stable transit flight - Jo, Daeil; Kwon, Yongjin (International Journal of Mechanical Engineering and Robotics Research, 2019)
With the rise of the public interests in the UAVs, the UAVs are becoming one of the important technological areas of the 4th industrial revolution era. For the UAVs, the fixed-wing type is advantageous, because it has a longer flight time than the multi-copter type, along with the faster speed. However, it requires a separate, lengthy, obstacle-free landing area, which can be difficult to find in the urban area. Additionally, it is not easy to safely land the fixed-wing type UAVs. Because of this, demand for the VTOL-type UAV is on the rise. The purpose of this study is to design and develop a VTOL capable of vertical landing and lift-off, as well as having appropriate thrust and lift during vertical, horizontal, and transition flights. We developed a formalized UAV development process, to provide a theoretical guideline to the development process. In order to determine the aerodynamic characteristics of the VTOL, we employed the 3D CAD & CAE methods, which can simulate the wind tunnel test for the optimal aerodynamic efficiency. Using the developed process, we determined the criteria for the internal modules that constitute the UAV, and we could assemble the airframe, considering the proper center of gravity. We conducted the SW setting for the flight adjustment and able to carry out the flight test accordingly. In the flight experiment, it was found that the developed process was adequate to provide a guideline to the successful design of the VTOL-type UAV.
Keywords: Aircraft design; Drone; Fixed wing; Multi-copter; Rotary wing; Transition flight; UAV; VTOL